The bone garden and other stories - Panda, Manoj Kumar (Rupantar, 2009)
When the gods disappeared -- The alphabet garden -- The tiger hunt -- Filling in the blanks -- The quest for a lost game -- Kaniska on the Scaffold -- The aesthetics of a supercyclone -- The tale of a dreamer's woe -- The yawn -- In the shadow of the tamarind -- Kasturi Das -- Gopa's walpolian world -- The bone garden